Embracing the Change: Homeopathy’s Role in Post Menopausal Wellness (Homoeopathy for All, 2025)
Post-menopause is a critical phase  in a woman’s life characterized by  the cessation of menstruation and  a wide range of physiological and  psychological changes. Common  symptoms include hot flashes, night  sweats, mood fluctuations, sleep  disturbances, and decreased bone  density. While conventional hormone  replacement therapy (HRT) remains  a standard treatment, it carries  potential risks and contraindications  for some women. Homeopathy, a  holistic system of medicine, offers  an individualized approach that may  provide symptomatic relief with  minimal side effects. This article  reviews the role of homeopathy  in managing postmenopausal  symptoms, highlights key remedies  such as Lachesis, Sepia, Sulphur, and  Calcarea carbonica. The potential  of homeopathy as a complementary  or alternative option is explored,  emphasizing the importance of  individualized remedy selection  and patient-centred care. Further  research is encouraged to validate the  efficacy and safety of homeopathic  interventions in postmenopausal  health.
Keywords: Homoeopathy; post menopause; Hormonal replacement therapy; women